Comparison of Standard Dressing and Chlorhexidine Gluconate-impregnated Dressing for the Prevention of Catheter-related Bloodstream Infection in Our Pediatric Intensive Care Unit - Nagehan Aslan; Dinçer Yıldızdaş; Ayşe Menemencioğlu; Filiz Korkmaz; Özden Özgür Horoz; Özlem Özgür Gündeşlioğlu (Galenos Yayinevi, 2020)
Introduction:Central venous catheters are frequently used for intravenous applications and hemodynamic monitoring in pediatric intensive care units. In addition to the benefits of the catheters, they can lead to many complications such as catheter-related bloodstream infection (CRBI). One of the most important steps in the prevention of CRBI is nursing care. Here, we compared CRBI rates between standard dressing and chlorhexidine gluconate-impregnated dressing in our pediatric intensive care unit.Methods:A total of 144 patients, who underwent central venous catheter and hemodialysis catheter placement, were included in the study. The patients were divided into two groups as standard dressing and chlorhexidine gluconate-impregnated dressing. The diagnosis of CRBI and colonization was made using the diagnostic criteria of the Center for Disease Control and Prevention.Results:The total number of central catheter days was 3749 in our pediatric intensive care unit during the study period. The CRBI rate was 4.53/1000 central venous catheter days. In the whole group, the CRBI rate was 10.4% and colonization rate was 11.8%. CRBI was detected in 13 patients (12.3%) with standard dressing and 2 patients (5.1%) in the chlorhexidine gluconate-impregnated dressing group. There was no statistically significant difference in CRBI risk and catheter colonization between the groups (p=0.356 and p=0.616, respectively).Conclusion:The rate of CRBI and colonization in the chlorhexidine gluconate impregnated dressing group was found to be lower than in the standard dressing group although not statistically significant. We believe that studies with larger patient groups will contribute to the literature.